Teacher Professional Development in Multicultural and Religious Contexts: Challenges and Opportunities in Indonesian Education - Abdul Jalil; Kelly Freebody (IJCRE - International Journal of Culture, Religion, and Education, 2026)
Indonesia’s education system operates within a uniquely multicultural and multireligious context that presents both challenges and opportunities for teacher professional development (TPD). Teachers are expected not only to master pedagogical and subject-matter competencies but also to foster tolerance, inclusivity, and social cohesion among learners from diverse cultural and religious backgrounds. This article examines teacher professional development in Indonesian education, focusing on how multiculturalism and religious diversity shape teachers’ professional learning experiences in the post-reform and post-pandemic era. Using a qualitative literature-based research design, this study synthesizes findings from recent empirical and theoretical studies on teacher development, multicultural education, and religious values in schooling. The results indicate that while Indonesian teachers face structural challenges such as limited training access, curriculum standardization, and ideological tensions, there are significant opportunities through culturally responsive pedagogy, faith-based ethical frameworks, and community-oriented professional learning. The study argues that effective TPD in Indonesia must integrate pedagogical competence, multicultural sensitivity, and religious moderation. This article contributes to the discourse on teacher education by offering a contextualized framework for professional development in pluralistic societies.